Rancang Bangun Media Pembelajaran Mobile Interaktif Menggunakan Smart App Creator pada Mata Pelajaran Dasar-Dasar Teknik Elektronika Kelas X SMK Negeri 2 Solok - Rara Cantika; Agariadne Dwinggo Samala; Dedy Irfan; Ika Parma Dewi (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
The aim of this research is to produce learning media mobile interactive on the Basics of Electronics Engineering subject which is valid and practical for class X students at SMK Negeri 2 Solok. The method used in this research is method Research and Development (R&D) with a 4D development model consisting of 4 stages, namely Define (Definition), Design (Planning), Develop (Development), and Disseminate (Dissemination). This research uses an instrument in the form of a questionnaire. This questionnaire will be filled out by material experts and media experts in the validity test and filled in by students in the practicality test. Based on data acquisition and processing, this research obtained the following results. First, the results of material validation by material experts are in the "Valid" category with a total validity value by the three material validators of 0.967 and the results of media validation by media experts are in the "Valid" category with a total validity value by the three media validators of 0.967. Second, at the practicality test stage by students involving 15 students obtained a practicality percentage of 95.67% which was categorized as "Very Practical". Based on the results of this research, it can be concluded that interactive mobile learning media using Smart App Creator is suitable for use as interactive learning media in learning because it has been proven to be valid and practical.